Development of a device for multi-modal mechanical manipulation of cells in 2D and 3D engineering environment - Sam, Jerry (Department of Human Biology, 2019)
All organisms from bacteria to cells within the human body experience some form of mechanical stimuli. The biochemical response from mechanical stimuli is known as mechanotransduction. Cell manipulation devices provide an understanding of mechanotransduction and the various signalling mechanisms that take place. The objective of this Master’s thesis was to develop a device for multi-modal mechanical manipulation of cells in 2D and 3D environments. The device is to mimic the stress conditions or the mechanical environment of the cells in vitro. The mechanical cell loading device will be used to perform cellular mechanical experiments to assist in other future biophysical research and investigate the mechanics of cells under various degrees of tension, compression and shear so that a better understanding of mechanotransduction can be obtained. Cells are seeded in a biocompatible medium and their force response is observed. The incorporation of tension, compression and shear stress in a single device constitutes the uniqueness of this designed device. A cell manipulator device was designed and assembled with different modular attachments for the various kinds of stress loading. The dimensions of the device were selected in a manner to enable the device to be mountable on a microscope for live cell imaging. The Carl Zeiss LSM510 Confocal Microscope was the microscope available for the experimentation. In this project, live cell imaging is only possible with tensile strain. Thus, the tension system was the predominant focus. Live cell imaging during tension provides accurate information about cellular morphology. Three different types of PDMS membranes were designed, manufactured and tested by applying a tensile load from the designed device. The three types of PDMS membranes produced were: 20 mm x 20 mm, 20 mm x 20 mm with 1mm thickness dividers (dividers divided the PDMS membrane into 4 even sized quadrants), and 10 mm x 10 mm. Strain characterisation of the three types of PDMS membrane was performed. The PDMS membranes are marked with ink from a permanent marker which serves as a frame of reference for strain measurement. Using the permanent marker, dots were marked in grid format. The PDMS membranes were subjected to tensile stress from the designed device under a confocal microscope. Length deformation of the markers along the stretch axis was measured and recorded during the practical experimentation. Using FEA software, FEA models of each type of PDMS membrane was simulated. The purpose of the FEA models is to facilitate the future studies of researchers. FEA simulations provide feedback to guide actual cellular experimentation for researchers. The FEA models of the various types of PDMS membranes were validated against the practical experimentation of strain characterisation. From the analysis and discussion of the results of FEA and practical experimentation, the designed device satisfies the objectives of this project. The device was most successful with the 20 mm x 20 mm PDMS membrane type since it showed close correlation to the ideal strain output. FEA simulation of the 20 mm x 20 mm PDMS membrane also showed close correlation to the experimental results. But, in the instance of the 10 mm x 10 mm PDMS membrane, experimental results of the strain output did not correspond with the user strain due to the clamping mechanism unable to grapple PDMS membrane appropriately. Thus, validation of the FEA 10 mm x 10 mm PDMS membrane was not successful.